The Impact of Transformational Leadership on the Effectiveness of Human Resource Management - the Mediating Role of Organizational Atmosphere and Organizational Change - A, Gemo; Phrompitakkul, Wasin (Journal of Dhamma for Life, 2024)
There are many factors that affect the effectiveness of human resource management, among which the leadership style of a leader is closely related to the effectiveness of human resource management. This article focuses on three very important variables: transformational leadership style, organizational atmosphere, and organizational change, and then constructs a basic framework with transformational leadership style as the independent variable, organizational atmosphere and change as the mediating variables, and human resource management efficiency as the dependent variable.